Cu2+ Ions in Fluoro Borate Glasses Studied by EPR and Optical Absorption Techniques - Ch. Srinivasuand, M. Ravichander (International Journal of Advanced Science and Technology, 2021)
EPR and optical absorption studies on xLiF-(30-x)Li2O-20SrO-50B2O3 system with 0 ≤ x ≤ 20 mole % glasses containing Cu2+ spin probe have been carried out. The glass transition temperatures are observed decreasingwith increase in LiF content in the composition. Peak-free X-ray diffractograms and homogeneous plain SEM image confirm the glassy nature of the prepared samples. Spectral studies were carried out to understand the effect of modifier oxide (SrO) and transition metal (TM) ion Cu2+ in the glass network. The EPR spectra of Cu2+ in all the glass samples recorded in the X-band frequency havesimilar spectral features. From the EPR spectra, spin-Hamiltonian parameters were evaluated. It was observed thatthe ground state of Cu2+ is dx2- y2 and the site symmetry around Cu2+ ions is tetragonal distorted octahedral. The optical absorption spectra exhibited a broadband corresponding to the d-d transition bands of Cu2+ ion. By correlating EPR and optical data, the bond parameters were evaluated and the values show purely ionic nature for the in-plane σ bonding and in-plane π bonding. The out-of-plane π bonding is moderately covalent. All these variations clearly indicate the structural changes in the present glass systems with varying LiF content.